The digital selling handbook : grow your sales by engaging, prospecting, and converting customers the way they buy today - Stinnett, Bill (McGraw Hill-Ascent Audio, 2023)
Actionable advice for sales professionals and business owners for growing sales in today's increasingly virtual marketplace. Rapid changes in where and how people live, work, and do business in recent years, have triggered major shifts in how customers shop for and buy virtually everything! Sales and marketing professionals are faced with the harsh reality of rethinking their entire approach to engaging clients in today's virtual marketplace-or risk quickly becoming irrelevant. They need to rethink their entire sales approach-and Digital Selling Handbook shows them how to do it. This comprehensive guide builds listeners' understanding of customer psychology and buying behavior in the new digital-first world. It provides best practices for engaging customers using a variety of methods. Digital selling expert and founder of Sales Excellence, Inc., Bill Stinnett covers the entire sales and marketing process, showing how to: create a magnetic personal brand that attracts prospective customers; engage customers earlier in the buying process; develop an evergreen lead machine using strategies of world-class organizations; write articles, emails, and social media posts that trigger customer action; find and create new opportunities through outbound prospecting; and turn customer conversations into sales opportunities and revenue.